U.S. Copyright Renewals, 1976 January - June - Library of Congress. Copyright Office (Salt Lake City, UT : Project Gutenberg, 2004)
"U.S. Copyright Renewals, 1976 January - June" appears to be a systematic compilation of copyright renewal registrations and related entries, likely produced in the late 20th century. This publication serves as an archival record of works that have undergone copyright renewal, offering a valuable resource for researchers, historians, and legal professionals interested in intellectual property rights and the evolution of creative works. The opening of this work presents an extensive array of entries that list various copyrighted materials alongside their renewal statuses, authors, and publication information. Each entry provides details such as the title of the work, the author's name, and the renewal date, covering a diverse range of subjects from literature and art to educational materials and law publications. This meticulous catalog not only highlights the breadth of creative output during the registration period but also serves as a historical reference for understanding trends in copyright practices during the 1970s. (This is an automatically generated summary.)
Release date is 2004-03-01
Produced by Michael Dyck, Charles Franks, pourlean, and the Online Distributed Proofreading team, using page images supplied by the Universal Library Project at Carnegie Mellon University
Keywords: Copyright -- United States -- Catalogs